A atuação de uma equipe multiprofissional no apoio à educação inclusiva - Silva, Márcia Altina Bonfá da (2016)
The search for an educational inclusive system has driven the discovery of ways and practices that concretize the ideal of access equality, abidance and learning to all students that present special educational needs inside of the educational space. The services and professionals of support are aimed as favorable alternatives to the effectuation of this principle, aiming the schooling in ordinary class. Starting from the hyphotesis that these services of multiprofessional teams when exists in the school system, are recent, fragmented and inarticulated, in due to the bit experience owned with this kind of support in brazilian reality, the general aim of this study was to describe and analyze this kind of service and identify, with the professionals of the team, strategies to improve it. Therefore, the aim of this study was the performance of a multiprofessional team, formed by three phonoaudiologists, three psychologists and a pedagogue, who acted in five municipal schools in the inner state of São Paulo.The research methodology used was based on collaborative research. The first stage involved a documental study with the aim to characterize the performance’s context of the participants. In the second stage were made individual interviews, in order to describe and analyze the work developed by the participants. The third stage involved reflection about the team’s service with interventions based on meetings of focal groups, aiming to identify strategies to improve it. The fourth, and last stage included documental analysis of the new proposal of work organization made by the team, after finalized the intervention process. The collected data were submitted to analysis of thematic content, and was used as tool the Atlas-Ti Software. The results were organized in four parts, according to the stages of the study. The results of the stage I allowed to contextualize the historic of creation of the multiprofessional team’s school service. The results of the stage II describe the organization of the service and allowed to conclude that there is school demand by these specialists, service which is appreciated by the school. However, the expectation was about clinical services, such as, evaluation and direct attendance to the students. It was also identified the existance of two models of services’ installment, the clinical and the educational. In the stage III, the reflexive meeting’s results revealed the difficulties with the establishment of collective and colaborative practices of the team in the school, the necessity of definition of roles and the reflection about the school culture as a factor for changes. The results of the stage IV showed that the use of the collaborative research reflected in the final project of the reorganization team of the service which had include some of the guiding principles of multiprofessional teams’ work in the schools. It was concluded that the service of a multiprofessional team can contribute with the construction of more inclusive schools, since is lined in an unique philosophy of work and that there is a permanent continuing formation of the team in collaborative proposals. The work of specialists in school, although is not an ordinary practice in Brazil, has showed its efficiency in other contexts, when the support service to the school context is based on the model of Collaborative Consultancy School which aims to help the development of a philosophy education that offers greater educational opportunities for all students.